Biogeochemical potential of biomass pyrolysis systems for limiting global warming to 1.5 °C. (17th April 2018) - Werner, C; Schmidt, H-P; Gerten, D; Lucht, W; Kammann, C
Abstract: Negative emission (NE) technologies are recognized to play an increasingly relevant role in strategies limiting mean global warming to 1.5 °C as specified in the Paris Agreement. The potentially significant contribution of pyrogenic carbon capture and storage (PyCCS) is, however, highly underrepresented in the discussion. In this study, we conduct the first quantitative assessment of the global potential of PyCCS as a NE technology based on biomass plantations. Using a process-based biosphere model, we calculate the land use change required to reach specific climate mitigation goals while observing biodiversity protection guardrails. We consider NE targets of 100–300 GtC following socioeconomic pathways consistent with a mean global warming of 1.5 °C as well as the option of additional carbon balancing required in case of failure or delay of decarbonization measures. The technological opportunities of PyCCS are represented by three tracks accounting for the sequestration of different pyrolysis products: biochar (as soil amendment), bio-oil (pumped into geological storages) and permanent-pyrogas (capture and storage of CO2 from gas combustion). In addition, we analyse how the gain in land induced by biochar-mediated yield increases on tropical cropland may reduce the pressure on land. Our results show that meeting the 1.5 °C goal through mitigation strategies including large-scale NE with plantation-based PyCCS may require conversion of natural vegetation to biomass plantations in the order of 133–3280 Mha globally, depending on the applied technology and the NE demand. Advancing towards additional bio-oil sequestration reduces land demand considerably by potentially up to 60%, while the benefits from yield increases account for another 3%–38% reduction (equalling 82–362 Mha). However, when mitigation commitments are increased by high balancing claims, even the most advanced PyCCS technologies and biochar-mediated co-benefits cannot compensate for delayed action towards phasing-out fossil fuels.